2008
DOI: 10.1080/08958370801975329
|View full text |Cite
|
Sign up to set email alerts
|

Depletion of Liver Glutathione Levels in Rats: A Potential Confound of Nose-Only Inhalation

Abstract: Nose-only inhalation exposure chambers offer key advantages to whole-body systems, particularly when aerosol or mixed aerosol-vapor exposures are used. Specifically, nose-only chambers provide enhanced control over the route of exposure and dose by minimizing the deposition of particles either on the subjects skin/fur or on surfaces of a whole-body exposure system. In the current series of experiments, liver, brain, and lung total glutathione (GSH) levels were assessed following either nose-only or whole-body … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…Superoxide Dismutase (SOD) activity was determined as previously described by some resesarchers [17,18].…”
Section: Determination Of Superoxide Dismutase Activitymentioning
confidence: 99%
See 1 more Smart Citation
“…Superoxide Dismutase (SOD) activity was determined as previously described by some resesarchers [17,18].…”
Section: Determination Of Superoxide Dismutase Activitymentioning
confidence: 99%
“…This goes with a previous work by Raza et al, [20] that recorded decrease in brain GSH with concomitant increase in lipid peroxidation levels after gasoline exposure in plants. The decrease in glutathione levels due to inhalation of the organic chemicals is attributed to the oxidative stress induced by Fechter et al, [18].…”
Section: Glutathionementioning
confidence: 99%
“…l-Cysteine is a well-known sulfur-containing non-essential amino acid that is oxidized to cysteine (Lee et al 2013), which exerts antioxidant activities (Lee et al 2013;Elias et al 2005;Miura et al 2014). l-Cysteine is also important for glutathione (GSH), which is a key antioxidant molecule in cellular systems (Fechter et al 2008); accordingly, Jain et al (2016) reported that oral supplementation with l-cysteine upregulates circulating levels of GSH.…”
Section: Introductionmentioning
confidence: 99%
“…These effects have been seen in animals exposed to clean air in nose-only exposure tubes for varying lengths (van Eijl et al, 2006;Narciso et al, 2003). There is the potential for stress experienced by animals in nose-only exposure studies to affect the results of the study by affecting immune competence (Bernet et al, 1998;Jakab and Hemenway 1989) or xenobiotic metabolism (Fechter et al, 2008), or by modulating gene expression in key organs (Thomson et al, 2009;Ha et al, 2003;Laconi et al, 2000;Panuganti et al, 2006;Sato et al, 2006;Yin et al, 2006), although some did not find confounding effects (Rothenberg et al, 2000). The duration of a chronic toxicity study by the inhalation route will normally be 12 months and that for a carcinogenicity study will be 18-24 months, dependent on the species used (see also Section 3.3.3 of this guidance).…”
mentioning
confidence: 99%